(untitled) (TAJ: Journal of Teachers Association, 2023)
Introduction: A better prognosis has resulted from the use of molecular techniques in cancer diagnosis. The FGFR family of genes is one of the major gene families involved in the carcinogenic pathways of different malignancies. Tumorigenesis, uncontrolled cell proliferation, and a number of pathologic diseases are linked to improper FGFR activation. The family of genes known as FGFRs encodes cell surface membrane receptors with tyrosine kinases.The development of oral squamous cell carcinoma (OSCC) may be significantly influenced by fibroblast growth factor receptor 1 (FGFR1). Analyzing these elements’ expression patterns may provide fresh perspectives on illness management strategies including genetic mediated target therapy. Objectives: In order to improve care and prevent future difficulties from oral squamous cell carcinoma (OSCC), the current study sought to assess the expression of FGFR1 genes in OSCC tumors as a result of the discovery of biomarkers and early diagnosis. Methods:In order to assess the expression of FGFR1 genes in 16 OSCC samples, 16 normal specimens from the same sample, free from cancer margin and 4 control samples from other patient free from cancer, the Oral and Maxillofacial Surgery DepartmentatDental Unit of Rajshahi Medical College Hospital was collected. Trizol and the appropriate kits were used for RNA extraction and cDNA synthesis. Real-time PCR was used to assess the FGFR1 gene’s expression following the construction of a specific primer set in order to find and validate molecular biomarkers. The data is analyzed using the ANOVA and independent t-test. Statistics were shown to be significant when P<0.05. Results:According to the findings, there are notable variations in the expression of the FGFR1 gene between tumor and normal or control tissues (P < 0.001). Patients over 60 are more likely to have OSCC, and the majority of them smoke 8. Retromolar trigon 8 is the most frequent location, and the majority of them are in stages III and IV. The FGFR1 gene expression does not significantly differ according on a patient’s age, gender, religion and behavior, including whether they smoke, drink, or chew paan. It also does not differ depending on the tumor’s location, stages and grade. Conclusions: The FGFR1 gene was often expressed differently in cancerous and control tissues, confirming the gene’s involvement in OSCC. The expression of FGFR1 is not correlated with factors such as gender, age, history of smoking, alcohol intake, chewing paan, tumor site, degree of differentiation, or TNM stage. The current investigation demonstrated the critical function of the investigated gene in the diagnosis of OSCC. To verify this, though, more research is required. TAJ 2023; 36: No-2: 155-162